The historiography of yellow fever in latin america since 1980: The limits of presentism (2019)
This article provides a historiographical analysis of yellow fever in Latin America. It shows that the dominant narratives approach the fever using the natureculture dichotomy, either treating the fever as an historical actor or linking its history to power relations. This study explores some histories that associate the disease with the racialization of public health discourse, the relationship between centers and peripheries in the production of science, and US public health. It argues that this historiography fixes the nature of the fever according to contemporary medical knowledge (presentism), and suggests that new themes and perspectives might emerge from a dialogue with the history and sociology of science. © 2017, SciELO-Scientific Electronic Library Online. All rights reserved.